Ekopedagogik Dalam Menumbuhkan Kesadaran Ekologis - Matroni; Hasan Basri (TA'DIB: Jurnal Pendidikan Agama Islam, 2024)
Education from an early age or pre-school to build Indonesian citizens' awareness of the need to preserve cultural and biological diversity. Ecological education is one of the keys. Ecology is a multidisciplinary science. The science of ecology is currently being discussed due to the development of development in various countries which causes catastrophic environmental damage and results in a decrease in the carrying capacity of the environment and the quality of human life in areas where the environment is damaged. Based on this research, this research uses a type of qualitative research with data collection procedures in the form of interviews, observations and documentation of respondents who have relevance to the research objectives, the data that has been collected from field research is then analyzed descriptively-interpretive. Interpretation by researchers is carried out based on formulations oriented to the actors or people studied (emic analysis). Thus interpretive analysis is carried out with interpretations of what informants say, or thinking about what they say, which then organizes it all in a research report.